Bibliometric analysis of performance assessment research trends in Asia - Alimunddin, Alimunddin; Usman, Asri; Safitri, Ela; Kusniawati, Kusniawati (MID Publisher International, 2025)
This study aims to map research trends on performance assessment in the Asian region through a bibliometric approach to scientific publications indexed in the Scopus database during the period 2014–2024. From the results of a systematic selection of 29 open-access articles, a productivity pattern was found that was highly concentrated in 13 major countries, namely China, India, Japan, South Korea, and Indonesia, which consistently contributed more than 85% of publications. This finding suggests a strong correlation between the ratio of R&D investment to GDP and the output and impact of scientific journals. The average annual publication growth of 16–17% reflects the increasing attention to the issue of performance evaluation as a tool for organizational accountability and effectiveness. This study provides important implications for efforts to strengthen national research capacity, develop regional collaborations, and develop a more inclusive and evidence-based research agenda. Limitations of this study include the limited data coverage of open-access articles in Scopus and the absence of a qualitative approach to the social impact of research. Further research is recommended to expand data sources and incorporate mixed approaches to gain a more comprehensive understanding of the dynamics of performance assessment research in Asia.